Effect of thermocycling on the micro-tensile bond strength between self-adhesive resin cement and nonphosphate monomer cements on zirconium-oxide ceramics - S Sathish; S Lakshmi; Pia Patel; H Annapoorni (Wolters Kluwer Medknow Publications, 2019)
Objectives: The objective of the present study is to evaluate the bond strength of: (a) Zirconia blocks (tribochemical treatment and zirconia primer) and resin blocks bonded using self-adhesive resin cement (phosphate monomer cement). (b) Zirconia blocks and resin blocks bonded using nonphosphate monomer cement. (c) Micro-tensile bond strength of zirconia and resin blocks, bonded with self-adhesive resin cement and nonphosphate monomer cement after thermocycling. Materials and Methods: Twenty zirconium-dioxide specimens (5 mm × 5.4 mm × 13 mm) were produced using a metal mold. Each zirconium block was duplicated in light-curing resin material specimen (5 mm × 5.4 mm × 13 mm) using a mold made of addition silicon impression material. A total of 40 specimens were made, of which 20 specimens were zirconia blocks and 20 were resin blocks, which would be bonded to each other using phosphate monomer-containing cement (Multilink [10 nos.]) and nonphosphate monomer-containing cement (RELY-X [10 nos.]). The specimens were then divided into two groups of n = 10 each. The surface of zirconium specimen of one group (Group 1) was treated with zirconia primer and bonded with phosphate monomer-containing cement, and the other groups (Group 2) were not treated with any surface conditioning and were bonded with a nonphosphate containing cement. The specimens in each group were further subdivided into two subgroups of n = 5 each as follows: Group 1-1A (subjected to thermocycling), 1B (nonthermocycled) and Group 2-2A (subjected to thermocycling), 2B (nonthermocycled). Then, they were subjected for testing of tensile bond strength under a universal testing machine. Results: Resin cement selection seems to be a more relevant factor in the bonding of zirconia. The phosphate monomer-containing cement has the better bond strength after thermocycling compared to the nonphosphate monomer group. Thermocycling reduced the bond strength of both the groups and a significant difference was seen in the bond strength of nonphosphate monomer cement group subjected to thermocycling compared to the nonthermocycled one. Tensile bond strength values were significantly affected by the luting agent system employed and by thermal aging. Hence, for long-term durability, luting of zirconia with a phosphate monomer-containing cement after the zirconia has been surface treated is preferable as their bond strength did not show much significant difference after being subjected to thermocycling, compared to the nonthermocycled group. Conclusion: Resin cement selection seem to be a more relevent factor in the bonding of zirconia thermocycling does affect adhesion to to zirconium oxide ceramics.